2022
DOI: 10.3389/fpsyg.2022.954996
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase young people's interest in STEM. A scoping review

Abstract: The underrepresentation of young people and particularly young women in many STEM fields has inspired various intervention programmes and research intended to boost their interest in these areas. The purpose of this scoping review is to examine the characteristics and effectiveness of interventions designed to encourage interest in STEM among secondary school students, particularly female students, over the past 20 years. A systematic search of the literature in five databases and additional search strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Some studies that have used a hybrid pedagogical model are recorded, combining gamification with other pedagogical models. Emotion (51,23); educational (48,85); game (38,8); achivers (38,44); digital (36,48); opportunity (29,36); exercise (28,79); design (27,83); practice (25,43); link (18,08); scenario (17,93); collaborative (16,28); inclusive (15,36); positive_emotion (15,36); help_students (14,42) This study showed that conventional exercises were detrimental to middle and high achievers' learning emotions, although their concepts improved (…).…”
Section: This Phenomenological Research Aims To Explore Physics Teach...mentioning
confidence: 91%
See 2 more Smart Citations
“…Some studies that have used a hybrid pedagogical model are recorded, combining gamification with other pedagogical models. Emotion (51,23); educational (48,85); game (38,8); achivers (38,44); digital (36,48); opportunity (29,36); exercise (28,79); design (27,83); practice (25,43); link (18,08); scenario (17,93); collaborative (16,28); inclusive (15,36); positive_emotion (15,36); help_students (14,42) This study showed that conventional exercises were detrimental to middle and high achievers' learning emotions, although their concepts improved (…).…”
Section: This Phenomenological Research Aims To Explore Physics Teach...mentioning
confidence: 91%
“…Game_Base_Learning (17,17); argumentation (13,31); discipline (13,31), competence (11,47); subject (11,16); art (10,95); computational thinking (10,34); creativity (9,23); inquiry_based (8,99); web (8,98); workshop (8,91); classroom (8,1); laboratory (7,82); STEAM (7,36) Soil (-9,6); learner (-8,88); Covid_ 19 (-8,6); platform (-7,87); robotic (-7,59); center (-7,59); emotion (-7,34); social (-7,03); flow (-6,58); genetic (-6,39); qualitative (-5,23); theory (-5,1); selfefficacy (-5,06); mental (-5,06); disability (-5,06); learning_efectiveness (-4,89) 2020-2023 escape_room (25,02); emotion (20,16); flow (16,67); genetic (10,45); theory (9,62); narrative (9,06); factor (9,04); need…”
Section: -2019 Student_engagement (2401);mentioning
confidence: 99%
See 1 more Smart Citation
“…Methodological reviews are particularly important in MMR intervention research because some basic procedures of the methodology are still not being implemented properly, as revealed by a number of reviews (see Section “Introduction”). The studies included in this methodological review were identified through a scoping review of intervention studies aimed at increasing young people’s interest in STEM ( Sáinz et al, 2022 )—hereinafter referred to as the original review . Specifically, we focus here on the subsample of studies from the original review that used MMR.…”
Section: Methodsmentioning
confidence: 99%
“…Students' increasing interest in science has been sparked by the Internet and the perception of having greater job security than other sectors [10]. Unfortunately, students' interest in science does not guarantee their automatic selection of a career in Science or Technology, so additional interventions should be made [11]. In any event, it can be said that the Internet is facilitating things previously popularized in specialized books.…”
Section: Theoretical Backgroundmentioning
confidence: 99%